2018
DOI: 10.2478/fhort-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic effect on fruit production and quality, antioxidant content and elemental composition of organically grown Physalis angulata L. and Physalis pubescens L.

Abstract: Research was carried out in northern Europe (Russia) with the purpose of assessing the yield, quality, biologically active compounds and elemental composition of Physalis angulata and Physalis pubescens fruits. P. angulata cultivars ‘Konditer’ and ‘Konditer 2’ gave the highest yield and mean fruit weight (11.2 t ha−1 and 75 g, on average), whereas P. pubescens variety Zolotaya Rossip had the worst outcome as it produced the smallest berries (3 g). ‘Zolotaya Rossip’ fruits attained the highest values of dry mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Fruit samples were collected at the second truss harvest (6 and 9 November in 2017 and 2018 respectively) and transferred to the laboratory, where determinations of dry residue, soluble solids, organic acids (malic, oxalic, citric, isocitric), minerals (K, Ca, Mg, Na, P, S, NO 3 , Cl), lycopene, total phenols, total ascorbic acid, lipophilic and hydrophilic antioxidant activities were performed by using the following procedures: The dry residue was assessed in oven at 70 • C until constant weight; the soluble solids ( • Brix) at 20 • C on the supernatant obtained by centrifuging the raw homogenate, using a digital refractometer by Bellingham and Stanley, model RFM 81. The organic acids were determined as previously described [34]. The mineral elements were assessed according to Rouphael et al [35].…”
Section: Determinations Of Fruit Quality Mineral Composition and Antmentioning
confidence: 99%
“…Fruit samples were collected at the second truss harvest (6 and 9 November in 2017 and 2018 respectively) and transferred to the laboratory, where determinations of dry residue, soluble solids, organic acids (malic, oxalic, citric, isocitric), minerals (K, Ca, Mg, Na, P, S, NO 3 , Cl), lycopene, total phenols, total ascorbic acid, lipophilic and hydrophilic antioxidant activities were performed by using the following procedures: The dry residue was assessed in oven at 70 • C until constant weight; the soluble solids ( • Brix) at 20 • C on the supernatant obtained by centrifuging the raw homogenate, using a digital refractometer by Bellingham and Stanley, model RFM 81. The organic acids were determined as previously described [34]. The mineral elements were assessed according to Rouphael et al [35].…”
Section: Determinations Of Fruit Quality Mineral Composition and Antmentioning
confidence: 99%
“…Ciplukan is a plant that is highly promising because it contains a variety of nutrients. Ciplukan fruit has varied mineral content consisting of calcium, potassium, magnesium, sodium, phosphorus, and nitrates [2]. Study by [3] also found high lipid, carbohydrate, and protein content in ciplukan fruit compared to the roots, leaves, and buds of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Ciplukan is extremely nourishing and rich in important minerals with macronutrients such as potassium, phosphorous, and magnesium (Golubkina et al, 2018), as well as micronutrients and vitamin C (Iwansyah et al, 2022). Flavonoids, phenolics, and chlorogenic acid are among the secondary metabolites of plants which are essential phytochemicals (Moreira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%